Analysis of Factors Influencing Nurse Performance in the Implementation of Nursing Care: A Literature Review: A LITERATURE REVIEW - Maria Candida Dos Reis; Muh. Abdurrouf; Ahmad Ikhlasul Amal; Dyah Wiji Puspita Sari (Indonesian Journal of Global Health Research, 2026)
Nurse performance is a key determinant of patient safety and quality of care, yet remains highly influenced by multidimensional internal and external factors. This literature review aims to examine and synthesize the theoretical and empirical evidence regarding the determinants of nurse performance in the implementation of nursing care. This review draws upon theoretical perspectives of organizational behavior, motivational theory, and competency-based performance, supported by empirical findings from research published between 2020–2025. Using the PRISMA 2020 method, 1,310 articles were initially identified, from which 11 studies met the inclusion criteria. The literature was systematically reviewed through a structured process involving database searching (PubMed, DOAJ, Google Scholar, Garuda, Sinta, and Scopus), screening based on predefined inclusion and exclusion criteria, independent data extraction by two reviewers using a standardized form, and methodological quality assessment applying the JBI Critical Appraisal tools. Given the heterogeneity of study designs, a narrative synthesis approach was used to categorize determinants of nurse performance. Evidence synthesis demonstrates that nurse performance is shaped by individual factors (competence, tenure), psychological factors (stress, anxiety, burnout), motivational variables (self-efficacy, intrinsic and extrinsic motivation), and organizational determinants (leadership, managerial support, work culture), alongside environmental conditions (workload, shift patterns, equipment availability). Competence, work motivation, effective leadership, and supportive work environments consistently enhanced nurse performance, whereas workload burden and pandemic-related stress were associated with performance decline. Methodologically, most studies relied on cross-sectional designs and subjective self-report instruments, limiting causal interpretation and standardization. Nurse performance is driven by an interplay of personal, psychological, organizational, and systemic factors, necessitating a holistic improvement strategy incorporating competency development, motivational support, leadership strengthening, and work environment optimization.